3D-bioprinted all-inclusive bioanalytical platforms for cell studies - Mazrouei, Roya; Velasco, Vanessa; Esfandyarpour, Rahim (Scientific reports, 2020)
Innovative drug screening platforms should improve the discovery of novel and personalized cancer treatment. Common models such as animals and 2D cell cultures lack the proper recapitulation of organ structure and environment. Thus, a new generation of platforms must consist of cell models that accurately mimic the cells’ microenvironment, along with flexibly prototyped cell handling structures that represent the human environment. Here, we adapted the 3D-bioprinting technology to develop multiple all-inclusive high throughputs and customized organ-on-a-chip-like platforms along with printed 3D-cell structures. Such platforms are potentially capable of performing 3D cell model analysis and cell-therapeutic response studies. We illustrated spherical and rectangular geometries of bio-printed 3D human colon cancer cell constructs. We also demonstrated the utility of directly 3D-bioprinting and rapidly prototyping of PDMS-based microfluidic cell handling arrays in different geometries. Besides, we successfully monitored the post-viability of the 3D-cell constructs for seven days. Furthermore, to mimic the human environment more closely, we integrated a 3D-bioprinted perfused drug screening microfluidics platform. Platform’s channels subject cell constructs to physiological fluid flow, while its concave well array hold and perfused 3D-cell constructs. The bio-applicability of PDMS-based arrays was also demonstrated by performing cancer cell-therapeutic response studies.